2023
DOI: 10.1111/jcmm.17703
|View full text |Cite
|
Sign up to set email alerts
|

Importance of fatty acid binding proteins in cellular function and organismal metabolism

Abstract: Fatty acid binding proteins (Fabps) are small soluble proteins that are abundant in the cytosol. These proteins are known to bind a myriad of small hydrophobic molecules and have been postulated to serve a variety of roles, yet their precise functions have remained an enigma over half a century of study. Here, we consider recent findings, along with the cumulative findings contributed by many laboratories working on Fabps over the last half century, to synthesize a new outlook for what functions Fabps serve in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…It can either activate or deactivate protein function. Previously, phosphorylation was associated with the regulation of FABP3 protein function in Homo sapiens . We also analyzed the putative amino acid residues that are sensitive to phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can either activate or deactivate protein function. Previously, phosphorylation was associated with the regulation of FABP3 protein function in Homo sapiens . We also analyzed the putative amino acid residues that are sensitive to phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, phosphorylation was associated with the regulation of FABP3 protein function in Homo sapiens . 42 We also analyzed the putative amino acid residues that are sensitive to phosphorylation. We found that serine and threonine are putatively involved in the phosphorylation of most of these proteins.…”
Section: Resultsmentioning
confidence: 99%